(untitled) (Development Engineering Conferences Center Articles Database, 2025)
Solar cells are the cornerstone of energy generation in aerospace engineering, providing reliable power for satellites, spacecraft, and emerging solar-powered platforms. This review explores the evolution and application of photovoltaic technologies in the aerospace sector, beginning with early silicon devices and advancing to state-of-the-art III–V multijunction, thin-film, and perovskite-based solar cells. Each technology is examined in terms of efficiency, specific power, radiation tolerance, mechanical robustness, and adaptability to the harsh space environment. Comparative analyses highlight the trade-offs among different cell types, while special emphasis is given to recent innovations leveraging nanotechnology to enhance performance and resilience in orbit. By synthesizing current research and future prospects, this article underscores the pivotal role of solar cells in enabling sustainable aerospace missions and outlines pathways toward next-generation photovoltaic systems for space exploration.